Penerapan Pendekatan Multidisiplin dalam Sistem Pendidikan Pondok Pesantren Annur 1 Bululawang Malang - Abd. Kholiq; Ahmad Sulusin; M. Nor Kholis; Muhammad Faiz Nurfalahi (CV. Lentera Literasi Indonesia, 2026)
This study aims to examine the concept, implementation, and impact of a multidisciplinary approach in the educational system of An-Nur 1 Islamic Boarding School in Bululawang, Malang, on the moral formation of students. The study used a qualitative method with a field study approach through observation, interviews, and documentation. Data were analyzed descriptively and analytically to understand the practice of integrating scientific values ​​in Islamic boarding school education. The results show that the multidisciplinary approach is understood as a moral-based educational strategy that places religious knowledge as the main foundation, supported by student psychology and educational science. This approach is implemented in formal learning, dormitory life, and non-formal activities operationally and contextually. The study concluded that the multidisciplinary approach contributes positively to the moral formation of students, although it still requires strengthening in the aspects of methodological formulation and systematic evaluation.